Major Forces Affecting Rural Regions in 2020 - David Freshwater (Wieś i Rolnictwo)
Rural regions in OECD countries have always faced development challenges, resulting from their: reliance on natural resources, small labour forces, and long distances from markets, as well as the effects of globalization. Now, in addition, their development opportunities are further constrained by: climate change requirements, increased economic fragility resulting from COVID and the lingering effects of the 2008 recession, and the uneven impacts of the Internet economy. But, from a rural development policy perspective, perhaps the most important new challenge is the rise of rural populism. While rural areas and people have long been seen as distinct from their urban counterparts, in the last two decades these gaps have grown. Importantly, while the internet and information and communications technology (ICT) were initially seen as providing opportunities to improve social cohesion and link rural and urban people and places, instead they seem to have increased tensions. Because the core values of urban and rural people have grown so far apart, it is more difficult to establish the political compromises that are required to form effective policy. Absent some reconciliation of these social and political differences, it is difficult to see how national government policy can evolve to meet new challenges. Consequently, the likelihood of national governments being able to identify and implement coherent rural development policies is reduced.